Intracranial Vertebrobasilar Artery Dissection Associated with Postpartum Angiopathy. (16th August 2009) - McKinney, James S.; Messé, Steven R.; Pukenas, Bryan A.; Satti, Sudhakar R.; Weigele, John B.; Hurst, Robert W.; Levine, Joshua M.; Kasner, Scott E.; Sansing, Lauren H.
Abstract : Background . Cervicocephalic arterial dissection (CCAD) is rare in the postpartum period. To our knowledge this is the first reported case of postpartum angiopathy (PPA) presenting with ischemic stroke due to intracranial arterial dissection. Case . A 41-year-old woman presented with blurred vision, headache, and generalized seizures 5 days after delivering twins. She was treated with magnesium for eclampsia. MRI identified multiple posterior circulation infarcts. Angiography identified a complex dissection extending from both intradural vertebral arteries, through the basilar artery, and into both posterior cerebral arteries. Multiple segments of arterial dilatation and narrowing consistent with PPA were present. Xenon enhanced CT (Xe-CT) showed reduced regional cerebral blood flow that is improved with elevation in blood pressure. Conclusion . Intracranial vertebrobasilar dissection causing stroke is a rare complication of pregnancy. Eclampsia and PPA may play a role in its pathogenesis. Blood pressure management may be tailored using quantitative blood flow studies, such as Xe-CT.